The Influence of Yoga Exercise on Mother’s Anxiety Pregnant Trimester III in the Working Area of the Puskesmas Alas - Herni Hasifah; Nur Arifatus Sholihah; Iga Maliga; Rafi’ah Rafi’ah; Ana Lestri (Sean Institute, 2023)
Antenatal care is one of the efforts that can be made by pregnant women so that the delivery goes smoothly with the aim of preparing for a physiological delivery so that the mother and child to be born are in good health. This research is a quantitative research. The population in this study were pregnant women who were in the working area of the Alas Health Center, totaling 30 people. The results showed that the highest level of anxiety for mothers before being given yoga exercises was at the level of severe anxiety (50%) and the level of anxiety for mothers after being given yoga exercises was mostly at moderate levels of anxiety (63.3%). And the results of the analysis show a 2-tailed value of 0.000, which means that there is an effect of yoga on the anxiety level of pregnant women.